Information hiding technique in most significant bit of still image - Fu Bing; Zhou Xiansan (2009 International Conference on Image Analysis and Signal Processing, 2009)
Information hiding techniques have received much attention in the fields of the copyright protection and covert communication etc. This paper proposes a new data hiding method in a still image. With color quantization technique, redundant space in a color still image is created, and the palette of the image is amended. Then secret information is embedded into the most significant bit of pixels of the still image, including the most significant bit and the second significant bit. The result of the experiment shows that the new information hiding technique has properties such as high security, strong robustness and high embedding capacity.